Smarter Aerodynamics - Aerodynamic improvement of Chalmers’ Shell Eco-marathon car Smarter - Ljungström, Filip; Ottosson, Martin; Saeed, Mohammed; Sundell, Emma; Trangsrud, Ida; Winqvist, David (My University, 2016)
Students at Chalmers have participated in the UrbanConcept class in the Shell Ecomarathon competition since 2009. The aim of the competition is to build and drive a car as far as possible with an amount of energy equivalent to 1 litre of petrol. Chalmers current car is called Smarter and has been manufactured at the university campus, meaning that there were some limitations regarding manufacturing possibilities. Therefore, a simple body design was chosen, consisting of flat plates made out of plastic material. This design was assumed to result in poor aerodynamic properties, which gave rise to this Bachelors thesis. The purpose of this thesis was to improve the aerodynamic properties of the car and thereby lower the air drag, without compromising the possibility of manufacturing it at Chalmers. This has been done through examining the properties of the original design with flow simulations in STAR-CCM+ and in a following design process improve the design from an aerodynamic perspective. Several designs were presented during the design process and the best designs were selected and presented in a final design. The final design has a drag coefficient of about 34% of the coefficient for the original design, which will contribute to a better fuel efficiency.
Keywords: Strömningsmekanik; Grundläggande vetenskaper; Transport; Fluid mechanics; Basic Sciences; Transport